2022
DOI: 10.1111/obr.13452
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the first global multidisciplinary consensus meeting including persons living with obesity to standardize patient‐reported outcome measurement in obesity treatment research

Abstract: Summary Quality of life is a key outcome that is not rigorously measured in obesity treatment research due to the lack of standardization of patient‐reported outcomes (PROs) and PRO measures (PROMs). The S.Q.O.T. initiative was founded to Standardize Quality of life measurement in Obesity Treatment. A first face‐to‐face, international, multidisciplinary consensus meeting was conducted to identify the key PROs and preferred PROMs for obesity treatment research. It comprised of 35 people living with obesity (PLW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The shift in this direction in research, clinical practice and industry is both acknowledged and a step in the right direction. [37][38][39][40] Within practice, there are numerous examples of the improvement of the construct of 'success'; as outlined by the use of 'Best Weight' developed by Arya Mitra Sharma and Yoni Freedhoff, and in the prioritised value of psychological aspects in dialogue. 40 It is also demonstrated in the pilot to apply the Canadian guideline, which incorporates more holistic aspects of success, to other countries (Chile and Ireland).…”
Section: Discussionmentioning
confidence: 99%
“…The shift in this direction in research, clinical practice and industry is both acknowledged and a step in the right direction. [37][38][39][40] Within practice, there are numerous examples of the improvement of the construct of 'success'; as outlined by the use of 'Best Weight' developed by Arya Mitra Sharma and Yoni Freedhoff, and in the prioritised value of psychological aspects in dialogue. 40 It is also demonstrated in the pilot to apply the Canadian guideline, which incorporates more holistic aspects of success, to other countries (Chile and Ireland).…”
Section: Discussionmentioning
confidence: 99%
“…The BODY-Q is a reliable and valid PROM for weight loss and/or BC patients that has been increasingly used to evaluate treatment outcomes worldwide. [17][18][19] Recently, we published the general population normative scores for interpreting the BODY-Q. 20 In this study, the psychometric properties of the BODY-Q were investigated in the normative population, to evaluate how data fit the Rasch model and to assess the evidence to support the use of a common scoring algorithm for international use.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Recent literature showed that the BODY-Q stood out as the PROM with the highest level of validation evidence for use in weight loss and BC patients. [17][18][19] Recently, our team published general population normative values from 12 European and North American countries to enable interpretation of the BODY-Q scores for clinical research and care. 20 Scores from the general population enables a better understanding of HRQL of obesity and change through the weight loss trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…18 Furthermore, the level of decision regret was compared with QoL scores, which were assessed using the BODY-Q, a widely recognized and reliable measurement instrument for QoL in bariatric surgery. 20,25 A number of potential limitations should be considered. First, the sample size of 115 patients is relatively small, and 52% of the patients did not It should be noted that this is the first study to investigate the level of regret in bariatric surgery using the DRS.…”
Section: Discussionmentioning
confidence: 99%